Prevalence of burnout and practice-related risk factors among dentists in Saudi Arabia - Ammar Talal Abdelrahman Asali; Fawaz Pullishery; Nada Mohammed Ibrahim; Wasmah Waheeb Tobji (Wolters Kluwer Medknow Publications, 2021)
Introduction: Dentists are exposed to a high level of stress at the workplace and are at higher risk of experience burnout. Burnout has profound consequences on quality of life, patient care, and also on the health-care system. Aim: The present study aimed to assess the prevalence of burnout among dentists and identify its relationship with the work-setting factors in Saudi Arabia. Materials and Methods: A cross-sectional online survey was conducted using a pretested and structured questionnaire. A mixture of convenience and snowball sampling was used to collect the responses from dentists using two versions of the 22-item Maslach Burnout Inventory Scale that had three domains: emotional exhaustion (EE), depersonalization (DP), and feeling of decreased accomplishment. Dentists with scores on EE ≥ or DP ≥10 were considered to have the manifestation of burnout. Results and Discussion: The prevalence of burnout in dentists was found to be 33.4% and Saudi dentists experienced more burnout than non-Saudi dentist (P < 0.05). Among different dental specialties, prosthodontists and endodontists showed more prevalence than any other specialties (P < 0.05). Dentists who worked in clinical settings and also who worked more than 40 h/week experienced more burnout than others (P < 0.05). Conclusion: The prevalence of burnout among dentists working in Saudi Arabia was found to be 33.45%, and it was significantly more among Saudi dentists than expatriate dentists. Occupational burnout among dentists is a serious problem and should be dealt with appropriate interventions such as stress management training, coping up skills, organizational or structural change to reduce workload, and effective use of leisure time activities.